Current concepts in osteoarthritis - de Rezende, Márcia Uchôa (Sociedade Brasileira de Ortopedia e Traumatologia Regional de São Paulo, 2013)
Osteoarthritis (OA), the most common form of joint disease, affects mainly the hips, knees, hands and feet, leading to severe disability and loss of quality of life, particularly in the elderly population. Its importance grows every year with the aging of the population, with a large increase in the elderly population compared to younger patients. The progressive understanding of the pathophysiology of OA, the perception that the process is not purely mechanical and / or aging, and clarification of the inflammatory pathways involved led recently to the clinical application of various drugs and other measures. This update aims to expose the current concepts on the pathophysiology and treatment of OA.